Sustainable entrepreneurship and renewable energy implementation in the agriculture sector of Trinidad and Tobago / Joshua Francis ... [et al.] - Francis, Joshua; Maharaj, Sandra; Boodlal, Donnie; Maharaj, Rean (Penerbit PRESS, Universiti Teknologi MARA, 2024)
As Trinidad and Tobago (TT) transitions to a higher dependence on renewable energy technology (RET) and increased sustainability, the agricultural sector and more specifically, agripreneurship is identified as a key area that would fuel this transition. In this paper, agripreneurship will be investigated to determine what barriers prevent the practices from being completely sustainable, as well as the opportunities for new sustainable entrepreneurship (SE) through the use of RET in this sector in TT. Studies on the status of agripreneurship locally and regionally, especially as it pertains to entrepreneurship and sustainability, are limited. Through the literature review on foreign jurisdictions and the identification of relevant factors unique to TT, a survey instrument was developed and validated. The survey instrument was administered to stakeholders in the small-scale agricultural sector, and the data was collected and analysed. The unique drivers for SE and RET implementation by small-scale farmers in TT were identified as education, economic, environmental, and social. The findings showed significant interest by farmers in learning about and implementing RET to benefit their farms. However, without direct incentives, training, education, financial support and investment by the government in RET for the sector, there is reluctance for utilisation. To begin RET implementation and increase SE, the systems in place for the dissemination of incentives and economic compensation must be fixed to run efficiently to build trust with farmers, so that they will utilise these incentives. Infrastructure for education and training designed specifically for small-scale farmers to learn about RET and SE must be put in place and utilised by farmers to tap into the potential in the technology industry. These findings inform policy development for the future RET implementation in the agricultural sector in TT.